In vitro study of antifungal effect of allicin on Aspergillus fumigatus ATCC 36607 growth - Sajali, Nurhayatie (2014)
Aspergillus fumigatus is a saprophytic fungus and it commonly affects immunocompromised hosts, leading to the development of invasive pulmonary aspergillosis. Mortality and morbidity rates due to aspergillosis are escalating over the past decades and the available commercial drugs come with adverse drug reactions. The fungal cell wall serves as an excellent antifungal drug target for development of new drugs due to its physiological features in providing mechanical strength, maintaining cell shape and integrity. Allicin, a pure compound extracted from garlic, has been proven to exhibit antimicrobial properties on a variety of microorganisms and the effect against A. fumigatusis of interest. The aims of this study were to examine the antifungal effect of allicin on A. fumigatus ATCC 36607, to assess the morphological alteration of the fungal cell surface and evaluate the expression pattern of cell wall related genes of A. fumigatus post treatment with allicin. The minimum inhibitory concentration (MIC) of allicin in A. fumigatus was determined by broth microdilution method according to the “Reference Method for Broth Dilution Antifungal Susceptibility Testing of Filamentous Fungi” (CLSI M38-A2) guidelines. The minimum fungicidal concentration (MFC) was determined by plating suspensions from optically clear wells from 96 well microtiter plate obtained in antifungal susceptibility testing onto Sabouraud dextrose agar (SDA). Changes in ultra structure on the cell surface were observed through scanning electron microscopy (SEM) at 1× MIC (3.2 μg/ml), 2× MIC (6.4 μg/ml) and sub-MIC concentrations which were ¼× MIC (0.8 μg/ml) and ½× MIC (1.6 μg/ml) respectively. Additionally, A. fumigatus was incubated at predetermined time points within 24 h period at 3.2 μg/mlin time kill assay. For gene expression analysis, A. fumigatus was incubated at MIC (1× MIC) and sub-MIC concentrations (¼× MIC and ½× MIC). RNA was then extracted and converted to cDNA. Amplification efficiency for each primer set was evaluated from 5-fold serial dilutions of cDNA. Gene expression was evaluated using Pfaffl method and statistical analysis was performed through Kruskal Wallis test. The present finding indicates that the MIC and MFC for allicin were both 3.2 μg/mL. Quantitative data in the form of optical density (OD) obtained indicated that p<0.05 at MIC value in comparison with untreated (growth) control. Complete suppression of hyphae formation at 3.2 μg/mL and reduced mycelial growth at 1.6 μg/mL and 0.8 μg/mL were observed through SEM. Alternatively, when A. fumigatuswas incubated with 3.2 μg/mL allicin in the time kill assay, the inhibitory effect of allicin was observed after 12 h incubation. Down regulation pattern of chsE, chsG, fksA, gelB, rhoAandrhoBgenes were observed at MIC and sub-MIC concentrations of allicin tested. With the exception for rhoA and rhoB, statistical analysis showed significant differences in the level of down regulation (p<0.05) at MIC and sub-MIC concentrations of allicin for chsE, chsG, fksA, and gel Bindicating significant effect on the expression of the genes during exposure to allicin. On the contrary, rhoD showed an up regulation expression pattern which significantly differed at MIC and sub-MIC concentrations of allicin (p<0.05). As a whole, the present finding strongly implied that allicin exerts its antifungal activity against A. fumigatus by inhibiting the fungal cell proliferation, hindering transformation of the conidia into hyphae and down regulation of cell wall related genes.